EXAMINATION OF EMOTION REGULATION STRATEGIES OF PRESCHOOL CHILDREN WITH DIFFERENT EMOTION REGULATION SKILLS - DİLBER , Mukadder and GÜNGÖR AYTAR, Abide (SSD Journal, 2022)
The aim of this research is to examine the emotion regulation strategies of children in the 5-6 age group who have different emotion regulation skills. Quantitative data of the research planned in the mixed model were collected from 73 children.The study group in which qualitative data were collected consisted of 16 children with low and high emotion regulation skills selected according to the outlier sampling method. In order to determine the emotion regulation skills of children, the Emotion Regulation Scale was used. Emotion regulation stories were told using puppets to reveal what children’s emotion regulation strategies were. Descriptive statistics were made on the data obtained from the Emotion Regulation Scale. In this way, children who scored above and below the average were identified. The data obtained from the opinions of the children were analyzed descriptively within the scope of the status selection, situation change, distraction, cognitive assessment, reaction adjustment and social support categories in the Emotion Regulation Process Model. While it was seen that all children with high and low emotion regulation skills used distraction from emotion regulation strategies, the cognitive assessment strategy was only used by children with high emotion regulation skills.